PERSEPSI MASYARAKAT TERHADAP KUALITAS PEMBELAJARAN ONLINE DI KOTA PEKANBARU - Prama Widayat; Ryan Pahlawan (UHN IGB Sugriwa Denpasar, 2022)
Shifting learning patterns during the early 2020 to the end of 2021, where face-to-face learning patterns in the classroom are used as online lectures from their respective homes. Starting from the level of kindergarten to college because of the case of the Covid-19 virus which was designated by the WHO as a pandemic. This is what underlies every country to make policies to reduce activities outside the home, such as offices and educational institutions. Especially in the field of education, this raises pros and cons among the community, especially for those who live in the middle to lower economic class, the costs they incur also increase to buy their children an Android phone, not to mention internet packages, so they have to teach children while taking care of household chores. , children are not disciplined because they play more outside the house, there is very little interaction at school with teachers even though this is very important to build the social spirit of students. With this condition, the perception of society, especially parents, prefers face-to-face schools because of the higher quality of knowledge gained than online.